Improved bio-oil yield and quality through fast pyrolysis and fractional condensation concepts - Álvarez-Chávez, Brenda J.; Godbout, Stéphane; Le Roux, Étienne; Palacios, Joahnn H.; Raghavan, Vijaya (Renewable Energy, Biomass & Sustainability, 2020)
Fast pyrolysis is a thermochemical process capable of producing biofuels that can replace fossil fuels. Pyrolytic oil can be used for electricity production, heating and chemical extraction (Fu et al., 2017; Kalargaris et al., 2017). However, the quality of bio-oil is limited by its low chemical stability associated with aging, low calorific value, high water content, high viscosity and high acidity (Alvarez-Chavez et al., 2019; Carpenter et al., 2014). Therefore, it is necessary to improve the quality of bio-oil before its use in our daily life. This study provides the evaluation of the effect of the operating conditions of a pyrolyzer reactor and its condensing system on the quality and yield of bio-oil. Response surface analysis was applied to optimize the quality and yield of bio-oil using four operational variables of the pyrolyzer. As a result, statistical models corresponding to the studied responses were obtained.